2011
DOI: 10.4248/ijos11075
|View full text |Cite
|
Sign up to set email alerts
|

Presence of Porphyromonas gingivalis in gingival squamous cell carcinoma

Abstract: Periodontal disease has been recently linked to a variety of systemic conditions such as diabetes, cardiovascular disease, preterm delivery, and oral cancer. The most common bacteria associated with periodontal disease, Porphyromonas gingivalis (P. gingivalis) has not yet been studied in the malignant gingival tissues. The objective of this study was to investigate the presence of P. gingivalis in specimens from squamous cell carcinoma patients. We have performed immunohistochemical staining to investigate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
147
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(154 citation statements)
references
References 25 publications
6
147
0
1
Order By: Relevance
“…P. gingivalis is a dysbiotic organism that is becoming increasingly associated with cancer, pancreatic cancer and OSCC in particular (18,19). P. gingivalis can be recovered from OSCC surfaces in significantly higher numbers than from contiguous healthy mucosa (72) and detected by immunohistochemistry in gingival carcinomas (73). Hence, the results of the present study suggest that noncanonical activation of ␤-catenin signaling by P. gingivalis may be a potential mechanism by which P. gingivalis could contribute to tumorigenesis.…”
Section: Discussionmentioning
confidence: 62%
“…P. gingivalis is a dysbiotic organism that is becoming increasingly associated with cancer, pancreatic cancer and OSCC in particular (18,19). P. gingivalis can be recovered from OSCC surfaces in significantly higher numbers than from contiguous healthy mucosa (72) and detected by immunohistochemistry in gingival carcinomas (73). Hence, the results of the present study suggest that noncanonical activation of ␤-catenin signaling by P. gingivalis may be a potential mechanism by which P. gingivalis could contribute to tumorigenesis.…”
Section: Discussionmentioning
confidence: 62%
“…They reported that P. gingivalis may cause mouth cancer and showed that P. gingivalis induced the alteration of epithelial cells to neoplastic forms and its concentration rate was higher among cancer cells than normal tissues of mouth. 20 According to Kang et al's study, there was a significant difference between the group of head and neck cancer patients and group of healthy individuals for the frequency of P. gingivalis. Contrary to our results, Kang et al's study revealed a higher prevalence of P. gingivalis among healthy individuals than cancer patients (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…Microorganisms and their products stimulate neutrophils, macrophages, lymphocytes and fibroblasts to produce reactive oxygen species (hydrogen peroxide and free oxygen radicals), reactive nitrogen species (nitric oxide), lipids and matrix metalloproteinase which finally leads to DNA damage in epithelial cells (1,47,48). Cytokines, growth factors and some other cellular mediators create an appropriate environment for cell proliferation and migration.…”
Section: Rational For the Relationship Between Malignant Lesions Of Omentioning
confidence: 99%
“…6-There is increasing evidence that Porphyromonas gingivalis are periodontal pathogens that exist within the specimens of squamous cell carcinoma (40,48). Porphyromonas gingivalis are important etiologic factors in periodontal disease found in a great number in the oral cavity of patients with poor oral hygiene or severe periodontitis (40).…”
Section: Rational For the Relationship Between Malignant Lesions Of Omentioning
confidence: 99%